Gangguan Menstruasi Menyebabkan Peningkatan Stres Akademik pada Mahasiswa: Menstrual Disorders Lead to Increased Academic Stress in College Students - Jehan Puspasari; Veronica Yeni Rahmawati; Dian Fitria (Fakultas Keperawatan Universitas Andalas, 2023)
Menstrual disorders are one of the causes of anxiety in the life cycle of women. Factors that influence include the environment, nutrition, drugs, physical activity, and stress. Adolescents have a tendency to experience menstrual disorders, and one of the factors is stress. Academic demands are a component that affects the level of stress in students. This research used a cross-sectional method with total sampling. The results of univariate analysis showed that the average age of menarche was 12 years, the average BMI was 20.50, good nutritional status was 66.7%, students did not experience menstrual disorders by 84.4% and the academic stress level of students was 80.9%. The results of the bivariate analysis showed a correlation coefficient of 0.635, with a p-value of 0.001 which means the higher the menstrual disorder, the higher the academic stress on students. These findings can be used to develop health promotion related to reproductive health in adolescent girls so as to reduce stress levels in students.